Intrusive advising and its implementation in residence halls - Tennant, Abigail (Kansas State University, 2013)
Abstract Intrusive advising is a concept that developed in the 1970s as a method of working with at-risk students by identifying challenges they faced and solutions to overcome them (Backhus, 1989). Intrusive contacts are those that make early, unsolicited contact with students in the hopes of identifying and resolving academic and social obstacles that would prevent persistence (Frost, 1991). This proactive approach has been experiencing revitalization in the current economic times due to declining funds and changing governmental funding models that would fund higher education on the basis of graduation rather than enrollment. Because 44 percent of first year students do not persist to their second year, this type of governmental funding model has profound implications for administrators (Bushong, 2009). I propose that administrators consider restructuring residence hall personnel responsibilities to include intrusive contacts in an effort to address retention issues. While residence hall personnel will not have the responsibility of scheduling classes, they can begin identifying and addressing issues earlier in the semester. This paper identifies several institutions that currently implement intrusive contacts in their residence halls and the benefits of doing so. These schools have indicated an increase in their students’ grades, commitment and persistence, and overall satisfaction since implementing intrusive contacts (B. Silliman, personal communication, November 1, 2012). The findings also revealed that residence halls with effective intrusive contacts involve collaborative efforts between student affairs personnel and faculty members, engage students in building rapport with staff early in their first semester, and focus on developing students holistically. This report provides a summary of best practices and strategies for implementing these contacts.
Keywords: First year students; Intrusive advising; Retention; Residence halls; Educational Administration (0514)